2023
DOI: 10.3389/fpsyt.2023.1193490
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional factors and cross-national postpartum depression prevalence: an updated meta-analysis and meta-regression of 412 studies from 46 countries

Abstract: BackgroundPostpartum depression (PPD) is the most common complication associated with childbirth and can lead to adverse outcomes for both mothers and their children. A previous meta-analysis found that PPD prevalence varies widely across countries. One potential underexplored contributor to this cross-national variation in PPD is diet, which contributes to mental health and varies significantly around the world. Here, we sought to update the global and national estimates of PPD prevalence using systematic rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 169 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…Chile, South Africa, and Hong Kong have the highest rates of postpartum depression, with prevalence rates of 38%, 37%, and 30%, respectively. 6 In our country, the prevalence of postpartum depression has been estimated to be 13-22% at 6-8 weeks postpartum. 7 Not only does postpartum depression have immediate adverse effects on the mother, baby, and her family, but it can also lead to long-term complications such as chronic or recurrent depression.…”
Section: Introductionmentioning
confidence: 99%
“…Chile, South Africa, and Hong Kong have the highest rates of postpartum depression, with prevalence rates of 38%, 37%, and 30%, respectively. 6 In our country, the prevalence of postpartum depression has been estimated to be 13-22% at 6-8 weeks postpartum. 7 Not only does postpartum depression have immediate adverse effects on the mother, baby, and her family, but it can also lead to long-term complications such as chronic or recurrent depression.…”
Section: Introductionmentioning
confidence: 99%
“…The global prevalence of PPD is 17.2% ( Fish-Williamson & Hahn-Holbrook, 2023 ). As with major depression, suicide associated with PPD has become the second leading cause of death among women ( Lindahl, Pearson & Colpe, 2005 ; Yu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many people with SUD experience other mental disorders. In the case of pregnant women, a growing number of studies have found that increased SSB consumption places them at higher risk of postpartum depression (PPD) 21 , 26 . This validates the experimentation of characterizing SSB as an SUD, for findings could help us make inferences about how it might affect PPD (Fig.…”
Section: Introductionmentioning
confidence: 99%